Improving Antimicrobial Stewardship in Acute Sore Throat: Comparison of FeverPAIN and McIsaac Scores with Molecular Point of Care Testing Using Abbott ID NOW - Rob Daniels; Tarek El Omda; Kinan Mokbel (Diagnostics)
Background: The diagnosis of streptococcal throat infection is an area where current practice results in significant over-diagnosis of bacterial infection, with the resulting implications for antimicrobial use and resistance. The use of molecular point of care testing (POCT) has previously been shown to alter antibiotic prescribing decisions when compared to Centor scoring. This paper explores the impact of the addition of POCT to clinical assessment using the McIsaac and FeverPAIN scoring systems. Methods: Retrospective analysis of the clinical records of 144 patients who had previously received point of care testing as part of a trial of POCT as an adjunct to usual care was undertaken. The McIsaac and FeverPAIN scores were calculated and then compared with the POCT result originally obtained. The records were also reviewed to identify further consultations within 10 days of being tested. Results: Sufficient clinical data were available to calculate the FeverPAIN and McIsaac scores in 81% of patients and outcome data were available for 96.5% of patients. For patients with a FeverPAIN score of 4 or 5, 50–67% of patients had a positive POCT result, while for patients with a McIsaac score of 4 or 5, 50–68% had a positive POCT result. Moreover, 16.7% of patients who tested negative, and 16.3% of patients who tested positive, had a further consultation within 10 days of being assessed. Conclusions: Although relatively few patients in this study had maximum scores on the FeverPAIN and McIsaac scoring, the addition of POCT was shown to alter antibiotic prescribing decisions in a significant number of patients, supporting the use of Abbott ID NOW point of care testing to reduce antibiotic prescribing. Larger studies are required to confirm these results and explore the health economic aspects and potential impacts on health inequalities.